When forests hold their breath: will increasing drought further disrupt carbon sequestration? - Chen, Yi-Ying; Simon Wang, S-Y; Yu, Hong-Wen; Liu, Wan-Yu (Environmental research letters, 2024)
The 2020–2021 record drought in Taiwan halted carbon sequestration in its predominantly evergreen subtropical forests. The analysis uncovers a significant correlation between net ecosystem exchange, radiative factors, groundwater levels, and wildfires, indicating that the severity of droughts leads to a shift from carbon absorption to emission in these forests, thereby inviting a broader examination of the climate–carbon nexus in future scenarios.